The economic costs and implications of high-technology hardware theft - Dertouzos, James N., 1950- (Rand, 1999)
This report presents the results of a study undertaken at the request of the American Electronics Association and a consortium of high-tech industries. Based on a nine-month survey of 95 firms, representing approximately 40 percent of the sales volume for the computer, semiconductor, hard disk drive, and cellular telephone industries, the authors estimate that direct costs of hardware theft are almost $250 million. Indirect costs (such as lost sales and expensive theft-reduction strategies) and industry losses could push total losses past $5 billion. Industry and consumers share the price of high-tech losses, but firms do not always have the economic incentive to invest in appropriate security measures. Since 1996, hardware theft has declined significantly, and recent security measures adopted by individual firms appear to be very cost-effective. The authors recommend more such investments and suggest that the largest payoff will come from anticipating what products are most vulnerable and devising targeted procedures to protect them. In addition, they recommend strengthening collaborative industry-law enforcement efforts to help track the threat, anticipate targets, and identify and disable stolen property. -- Provided by publisher.